1995
DOI: 10.1021/bi00031a007
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rubredoxin from Pyrococcus furiosus to Environmental Changes: Implications for the Origin of Hyperthermostability

Abstract: The bases of the hyperthennostability of rubredoxin from Py~ococcus furiosus (RdPf) have been probed by structural perturbations induced by solution pH and ionic strength changes. Comparison of the solution behavior at pH 7 and pH 2, as probed by far-and near-UV circular dichroism, Trp fluorescence emission, 1 -anilinonaphthalene-8-sulfonate (ANS) binding, and NMR spectroscopy, reveals the presence of only minimal structural variations at room temperature. At pH 2, the protein displays a surprising nearly nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 64 publications
(76 reference statements)
5
65
0
Order By: Relevance
“…EPR and CD Spectra of C. tepidum Rd-The near UV-visible CD spectra of oxidized C. tepidum Rd closely resembled spectra obtained previously (31,45,50), with the exception of the absorption maximum at 385 nm and the shoulder at 420 nm (Fig. 3A).…”
Section: Resultssupporting
confidence: 81%
“…EPR and CD Spectra of C. tepidum Rd-The near UV-visible CD spectra of oxidized C. tepidum Rd closely resembled spectra obtained previously (31,45,50), with the exception of the absorption maximum at 385 nm and the shoulder at 420 nm (Fig. 3A).…”
Section: Resultssupporting
confidence: 81%
“…Ion pairing also plays a role in protein stabilization (9). This was also confirmed by the determination of the structure of glutamate dehydrogenase (GDH) from Pyrococcus furiosus, which was compered with GDH from mesophilic origin.…”
Section: Introductionmentioning
confidence: 72%
“…High resolution structures of proteins from hyperthermophiles have shown that the number of ion pairs in most of the hyperthermophile proteins is higher than in mesophile counterparts (4 -13), although additional ion pairs were not observed in some hyperthermophile proteins (25)(26)(27)(28). Table III lists the following structural segments: five intra-helical, three inter-helical, two between helix and loop, one between helix and ␤-strand, one between ␤-strands, and one between ␤-strand and loop (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect of a surface salt bridge on the stability remains controversial even today; some reports have shown little contribution of a surface salt bridge to stability (14 -19), whereas others have shown a favorable contribution (20 -24). There are also reports on some hyperthermophile proteins without additional ion pairs (25)(26)(27)(28). The conformation of general globular proteins is marginally maintained by the combination of many positive (such as hydrophobic interaction and hydrogen bond) and negative (such as entropic effect and steric hindrance) factors for stabilization (29).…”
mentioning
confidence: 99%